Efektivitas Dinas Kesehatan Dalam Mengawasi Depot Air Minum Isi Ulang di Kabupaten Takalar - Srinur Hatijah; Rahman Syamsuddin (Law Department, Universitas Islam Negeri Alauddin Makassar, 2022)
The purpose of this research is to find out firs, how the effectiveness of the Health Office in supervising the refill drinking water depot in Takalar district. Second, what factors are preventing the Health Office frim overseeing the refill drinking water depot in Takalar district. This research is a type of qualitative research (field research) with anormative juridical approach anda an empirical approach. The data sources of this research are primary and secondary data sources whose data were obtained by conducting interviews with sanitarian officers at the District Health Office Takalar and several business owners of retill drinking water depots in the district Takalar. The data analysis technique used is qualitative analysis where the data is selected which is important and then classified based on the topic of discussion which will be described in a systematic and more detailed sentence form then a conclusion is drawn. The result of this study indicate that the supervision carried out by the Health Office towards the refill drinking water depot is not yet fully effective because there are still implementation of supervision that has not been implemented in accordance with the Permenkes. Number 736 of 2010 concerning Procedures for Supervision of Drinking Water Quality. The factors that hinder the Health Office in conducting supervision are limited budget, low level of awareness in maintaining environmental cleanliness by depot owners, depot owners do not want to obey officers, and refusal to inspect by owners of refilled drinking water depots.